TINJAUAN HISTORIS TENTANG DAULAT ABBASIYAH PADA MASA KEPEMIMPINAN KHALIFAH HARUN AL-RASYID (786-809 M) - Dian Amalia Chasanah; Maskun Maskun; Syaiful M (FKIP UNIVERSITAS LAMPUNG, 2013)
Daulat Abbasiyah standing after the collaps of Daulat Umayah, achieving the triumph in the leadership of the Caliph Harun Al-Rasyid. Therefore, this study aimed to find out the efforts made Caliph Harun al-Rasyid in achieving the triumph of Daulat Abbasiyah governor. The method used in this study is the historical method. Data collection technique is the technique of literature and documentation techniques, while the data analysis technique is a qualitative data analysis technique. From analysing that has been conducted by the author obtained results that efforts Caliph Harun al-Rasyid Abbasiyah Rule in achieving greatness in the leadership is to retain a vast territory, which is achieved by building fortified cities, a relationship with King Charlemagne, lifting Governors from the military, and sending spies. Caliph also seeks to strengthen the Rule of the Abbasiyah army to increase the number of military forces, forming a line specific health, as well as establishing an office supply or called Diiwan Al'Ardhi. As well as trying to improve the economy Caliph Abbasiyah Rule by establishing cooperative relationship with China, intensified the translation of the foreign literature, as well as applying tax and zakat payment.Keywords: Abbasiyah, Caliph Harun al-Rasyid, Effort